■ガウスと算術幾何平均(その37)
I(a,b)=∫(0,π/2)1/√{(acosφ)^2+(bsinφ)^2}dφ
J(a,b)=∫(0,π/2)dφ/√{(acosφ)^2+(bsinφ)^2}dφ
により定義する.
k=(a^2-b^2)^1/2/a,k'=(1-k^2)^1/2=b/a
とおくと
I(a,b)=1/a・K(k^2)
J(a,b)=a・E(k^2)=L
(a,b)=(1,k)のとき
I(1,k')=K(k^2)=π/2・F(1/2,1/2,1:k^2)
J(1,k')=E(k^2)=π/2・F(1/2,-1/2,1:k^2)
====================================
I(a,b)=I((a+b)/2,√ab)
すなわち、
∫(0,π/2)dφ/√{(acosφ)^2+(bsinφ)^2}=∫(0,π/2)dφ/√{((a+b)/2・cosφ)^2+(√ab・sinφ)^2}
2J((a+b)/2,√ab)=J(a,b)+abI(a,b)
====================================
α=liman,β=limbn
極限α=β=M(a,b)と表すと
M(a,b)=M((a+b)/2,√ab)
M(ca,cb)=cM(a,b)
π/2・F(1/2,1/2,1:k^2)=K(k^2)=π/2M(1,k')
M(1,√(1/2)=Γ(3/4)^2/Γ(1/2)=Γ(3/4)^2/√π
====================================